Vaccination following the expanded programme on immunization schedule could help to reduce deaths in children under five hospitalized for pneumonia and severe pneumonia in a developing country - Shahid, Abu Sadat Mohammed Sayeem Bin; Rahman, Ahmed Ehsanur; Shahunja, K. M.; Afroze, Farzana; Sarmin, Monira; Nuzhat, Sharika; Alam, Tahmina; Chowdhury, Fahmida; Sultana, Mst Shahin; Ackhter, Mst Mahmuda; Parvin, Irin; Saha, Haimanti; et al. (Frontiers in Pediatrics, 2023)
Pneumonia is the leading cause of under-five mortality worldwide. An expanded program on immunization (EPI) is one kind of evidence based tool for controlling and even eradicating infectious diseases. This study aimed to explore the impact of EPI vaccination, including BCG, DPT-Hib-Hep B, OPV, IPV, and PCV-10 among children 4-59 months hospitalized for pneumonia and severe pneumonia. Additionally, we evaluated the role of 10 valent pneumococcal conjugate vaccine alone on clinical outcomes in such children. In this retrospective chart review, children aged 4-59 months with the WHO defined pneumonia and severe pneumonia, admitted in the Dhaka Hospital of icddr,b between August`2013 and December`2017 who had the information on immunization as per EPI schedule by 4 months of age, were included in the analysis. Comparison was made between the children who were fully immunized (immunization with BCG, DPT-Hib-Hep B, OPV and IPV during 2013-2015 and PCV-10 during 2015-2017) and who were not immunized (consists of partial immunization and no immunization) during the study period. A total of 4625 children had pneumonia and severe pneumonia during the study period. Among them, 2605 (56.3%) had information on immunization. Between them, 2195 (84.3%) were fully immunized by 4 months of age according to EPI schedule and 410 were not immunized. In log-linear binomial regression analysis, it has been revealed that immunization in children 4-59 months of age was associated with lower risk of diarrhea (p=0.033), severe pneumonia (p=0.001), anemia (p=0.026) and deaths (p=0.035). Importantly, the risk of developing severe pneumonia (1054/1570 [67%] vs. 202/257 [79%], p<0.001) and case-fatality-rate (57/1570 [3.6%] vs. 19/257 [7.4%], p=0.005) were still significantly lower among those who were immunized with PCV-10 than those who were not. Children immunized as per EPI schedule were at a lower risk of diarrhea, severe pneumonia, anemia and deaths, compared to unvaccinated children. In addition, PCV-10 was found to be protective against severe pneumonia and deaths in such children. The overall results underscored the importance of the continuation of immunization scrupulously adhering to EPI schedule to reduce the risk of morbidities and mortalities in such children, especially in resource-limited settings.